2004
DOI: 10.1001/archsurg.139.7.780
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gastric Surgery on Systemic Ghrelin Levels in the Morbidly Obese

Abstract: Hypothesis: Circulating ghrelin, produced primarily in the stomach, is a powerful orexigen. Ghrelin levels are elevated in states of hunger, but rapidly decline postprandially. Early alterations in ghrelin levels in morbidly obese patients undergoing weight reduction surgery may be attributed to gastric partitioning. Design and Patients: Thirty-four patients underwent Roux-en-Y gastric bypass with a completely divided gastroplasty to create a 15-mL vertically oriented gastric pouch. Eight other patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 34 publications
6
71
0
3
Order By: Relevance
“…Many studies have shown gastric bypass operations to be associated with significant reduction of ghrelin levels (Cummings et al, 2002a;Geloneze et al, 2003;Lin et al, 2004;Roth et al, 2009;Stylopoulos et al, 2005;Suzuki et al, 2005). In addition, the normal, meal-related fluctuation and the diurnal rhythm of ghrelin level was found to be absent after gastric bypass surgery (Cummings et al, 2002a).…”
Section: Ghrelin and Bariatric Surgerymentioning
confidence: 99%
“…Many studies have shown gastric bypass operations to be associated with significant reduction of ghrelin levels (Cummings et al, 2002a;Geloneze et al, 2003;Lin et al, 2004;Roth et al, 2009;Stylopoulos et al, 2005;Suzuki et al, 2005). In addition, the normal, meal-related fluctuation and the diurnal rhythm of ghrelin level was found to be absent after gastric bypass surgery (Cummings et al, 2002a).…”
Section: Ghrelin and Bariatric Surgerymentioning
confidence: 99%
“…Laparoscopic sleeve gastrectomy provides not only a restrictive mechanism by reducing the intake of excessive food, but also causes a decrease in ghrelin serum concentration and causes a statistically significant reduction in hunger sensation when compared with other bariatric procedures [4,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Much is known regarding life with chronically reduced ghrelin levels because thousands of individuals have undergone Rouxen-Y gastric bypass surgery, which reduces ghrelin levels by 50-70% for weeks relative to weight-loss controls. Postsurgical ghrelin levels are even lower after total gastrectomy or sleeve gastrectomy (removal of the fundus) and remain so in the long-term (34)(35)(36)(37)(38)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). The Roux-en-Y gastric bypass and sleeve gastrectomy surgeries both produce massive weight reduction, greater than those of other surgical procedures that less effectively reduce ghrelin levels and improve the health of previously morbidly obese patients with low complication rates (37,78,79).…”
Section: Resultsmentioning
confidence: 99%